Revisiting community engagement in higher education in South Africa from a vantage point of the notion of third mission - Saidi, A.; Boti, Z. (South African Journal of Higher Education, 2023)
Globally, there is increasing realisation that the idea of universities as ivory towers detached from the societies and environments within which they exist and operate, is untenable in the twenty-first century. Instead, there are reasonable expectations that universities should contribute to the realisation of the Millennium Development Goals, promote human welfare, and generally make the world a better place. The notion of third mission provides a cogent philosophy and a pragmatic framework for universities to work towards fulfilling these expectations. The article unpacks and analyses the notion of third mission of universities. It also discusses probable reasons why, despite the notion gaining momentum and being accepted globally, it has not gained much traction in South Africa where the focus is on community engagement which is but one of the myriads of activities that falls with the gamut of the notion of third mission. It contends that universities in South Africa have not made significant impacts with their community engagement activities because of the limited scope and scale of implementation, among others. The article concludes by demonstrating that universities and the broader society in South Africa have more to gain if the universities were to consider institutionalising, planning and effectively implementing third mission programmes.